Estructura florística y su incidencia en la diversidad vegetal del bosque protector Murocomba año 2015 - Mite Fernández, Norberto Leandro (2016)
The present research to evaluate the floristic structure and its impact on plant diversity of "protective forest Murocomba. For which purpose five sampling units (UM) were established throughout the study area. To develop this objective sampling techniques and statistical analysis of data the forest diversity it was determined. In the sampling units with the use of indicators of diameter, total height of individuals, species, family abundance, frequency, dominance and index of the importance value (IVI) the floristic composition and structure of the vegetation was evident while for plant biodiversity in the Protected Forest Murocomba the diversity and similarity indices were used. A total of 38 families, 70 species and 440 individuals were recorded, being the most representative family Arecaceae and Solanaceae. The Ecological Importance Value Index within the sampling units of the study area allows to conclude that the most representative species are the Iriartea deltoidea, Brosimun utile and Wettinia quinaria with 24,59 %, 21,00 % and 20,05 % respectively. The vertical structure analysis revealed the multi-layered presence. The lower layer being the one with the most individuals, this means that there is minimal antropogenic intervention and a suitable susecional dynamics, an average diversity within the forest formation was obtained, in the UM1 and UM2 greatest diversity was recorded. The percentage of similarity between the sample units does not exceed 58,3 % of similar species in the formation of forest study, UM3 and UM5 were the greatest similarity recorded in this forest ecosystem. The results of the structure and plant diversity for wooded formation studied allows to conclude that there is heterogeneity between species within the different strata, and a proper process of ecological succession thanks to conservation measures and zero anthropic interventions in the past three decades.